Physicochemical Conditions of the Cidamar River Estuary in the Rainy Season with Management Implications - Hadiansah Hadiansah; Muhammad Muttaqien (Universitas Syiah Kuala, 2025)
The Cidamar River estuary is one of the major estuarine systems in Cianjur Regency, West Java, and is widely utilized by surrounding communities to support various activities such as agriculture, plantations, livestock farming, and daily domestic uses. This study aimed to analyze the physicochemical characteristics of the waters during the rainy season in the Cidamar River estuary, Cianjur Regency. The research was conducted from January to March 2022, which corresponds to the rainy season period. Water samples were collected from two sampling stations with an approximate distance of 1.5 km between sites. Physicochemical parameters were measured in situ using a Water Quality Recorder (LUTRON WAC-2019SD). The obtained data were analyzed and compared with established water quality standards. The results indicated that all twelve physicochemical parameters exhibited monthly variations. Several parameters, such as dissolved oxygen, were found to comply with the applicable water quality standards. Variations in the measured parameters were influenced by factors including seasonal conditions, sampling time, and anthropogenic activities around the study area. The findings of this study provide baseline information for the environmental management of the Cidamar River estuary to maintain water quality and ensure its sustainable use by local communities.